Collisionless Tearing Instability in Relativistic Nonthermal Pair Plasma and Its Application to MHD Turbulence - Ivan Demidov; Yuri Lyubarsky (The Astrophysical Journal)
Collisionless tearing instability with a power-law distribution function in a relativistic pair plasma with a guide field is studied. When the current sheet is supported by plasma pressure, the tearing mode is suppressed as the particle spectrum hardens. In the force-free limit, the instability growth rate becomes independent of the particle spectrum. We apply these results to relativistic MHD turbulence, where magnetic energy greatly exceeds plasma rest energy, and derive an expression for the transverse size of turbulent eddies unstable to tearing mode. We also establish the critical plasma magnetization parameter above which charge starvation prevents the tearing instability. These results might be useful for developing more accurate models of particle acceleration in relativistic astrophysical sources.